LINGKUNGAN PENGENDAPAN FORMASI PEMBAWA BATUABARA WARUKIN DI DAERAH KANDANGAN DAN SEKITARNYA, KALIMANTAN SELATAN - R Heryanto; H Panggabean (Jurnal Geologi dan Sumberdaya Mineral, 2013)
Kandangan area belongs to the South Hulusungai the District, South Kalimantan Province. The Warukin Formation in this area is situated in the eastern margin of the Barito Basin. In this area, the basin is underlain by Pre-Tertiary rocks comprising an assortment of rocks of continental and oceanic crusts. The Barito Basin was filled by sedimentary rocks of the Tanjung, Berai, and Warukin Formations having an age of ranging from Eocene to Miocene which was then unconformably succeeded by the Plio-Pleistocene Dahor Formation. The Warukin Formation consists of grey- to blackish color of claystone, intercalated by sandstone and coal seams. The thickness of coal ranges from 0.5 to 12 meters. The coal is black, dull to dull banded, light, contains abundant of resins and showing a woody structure. The Warukin coal seam composed by macerals of vitrinite (59.4-86.6%), exinite or liptinite (0.8-9.5%), and inertinte (3.4-17.4%). Based on a triangle diagram of TFD facies shows that coal samples of the Warukin Formation categorized into a wet forest swamp or telmatic facies. Furthermore, the plotting Gelification Index (GI) versus Tissue Preservation Index (TPI) the coal seams of the Warukin Formation was deposited in the transgressive phase, at limnic facies, to lower delta plain facies.Keywords : coal, maceral, Warukin Formation, Kandangan, Barito Basin